Religious Symbols in Interfaith Marriages: An Analysis Grounded in Alfred Schutz's Theory of Motives - Muhammad Luthfilhakim; Muhammad Chairul Huda (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2025)
Religious diversity within families has become an increasingly relevant social phenomenon in contemporary pluralistic societies. This study examines the display of different religious symbols in interfaith families as an effort to foster harmony, employing Alfred Schutz’s theory of social action motives, Roland Barthes’s theory of symbolic meaning, and Leon Festinger’s theory of cognitive dissonance. This research adopts a qualitative juridical-empirical approach that integrates legal and sociological perspectives. Primary data were obtained through in-depth interviews and direct observations involving five interfaith families residing in Tlogosari Hamlet, Banyukuning Village, Bandungan District, Semarang Regency. Secondary data were collected from legal regulations, academic literature, scholarly journals, and local archives related to interfaith marriage and religious symbolism. The findings reveal that the display of diverse religious symbols functions not only as an expression of individual identity but also as a medium of symbolic communication that strengthens emotional bonds and tolerance among family members. Cognitive dissonance arising from religious differences can be mitigated through adaptive mechanisms such as mutual respect, compromise, and the inculcation of universal values. The study concludes that religious symbols play a crucial social role in maintaining harmony within multireligious families. Future research is recommended to explore legal and educational dimensions in interfaith families more deeply, particularly regarding the transmission of religious values to children, to enhance understanding of social harmony and interreligious coexistence in Indonesia.